Strain variation in the frequency of Abelson murine leukemia virus- transformed fetal liver pre-B cells bearing complete immunoglobulin heavy chain rearrangements (The Rockefeller University Press, 1988)
Fetal liver Abelson pre-B cell lines obtained from CBA/Tufts.xid and (CBA/Tufts.xid x CBA/Tufts)F1 mice have complete VDJH rearrangements on at least one allele. Such high frequencies of VDJH rearrangements have previously been observed in adult derived but not fetal liver derived Abelson pre-B cell lines. Genetic analyses suggest that CBA/Tufts.xid carries an autosomal dominant gene(s) that determines the predominance of VDJH rearrangements among transformants. This autosomal gene(s) might affect the intrinsic development of the early B cell lineage in the fetus or the fetal microenvironment, expanding pre-B cells of the "more mature" VDJH phenotype.